Pengaruh Voucher Diskon dan Gratis Ongkos Kirim Terhadap perilaku Konsumtif ditinjau dari Perspektif Islam - Oktavia Putri Handayani; Tito Meitawati (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2024)
This study aims to analyze whether there is a significant influence between offering discount vouchers and free shipping on consumptive behavior. This type of research is descriptive research using a quantitative approach. The data collection tool used was a questionnaire which was distributed to 250 respondents to the Racun Shopee Karawang group. The results of this study indicate that there is an influence between free shipping vouchers and discount vouchers on consumptive behavior. This is a negative thing for the view of Islamic economics because Allah SWT has prohibited wasteful acts as stated in QS. Al Isro': 26-27.